Research Progress on TiB-Based Protective Coatings - MENG Lin, WANG Jingjing, ZHU Xinfa, MENG Yi, LU Hongmei, LI Wei (Cailiao Baohu, 2025)
To meet the demand for high cutting speeds and feed rates, in addition to requiring a substrate material with high-hardness,excellent coating materials are also essential for protection.In recent years, the modern industry has become increasingly stringent on the performance of materials,and traditional protective coatings have gradually reached their limits.Both nano-multilayer coatings and nanocomposite coatings can effectively compensate for the performance deficiencies of single-layer coatings in terms of hardness, corrosion resistance and wear resistance, which make them widely studied in the field of protective coatings.This paper reviewed recent research progress in titanium boride-based hard coatings,the performance of doped titanium boride-based coatings has been improved to varying degrees.Compared with single-layer coatings, nano-multilayer and composite coatings have superior performance, so the future research directions were also prospected.